Estimation of Warm-Up Period Required for Heat Transfer of Heating Device Used for Heat Supply of Field Hospital Operating in Conditions of Extreme Situations - A. P. Nesenchouk; N. S. Koneva; I. P. Iokova; T. V. Ryzhova; D. I. Shklovchik; M. A. Yarmolchik (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2013)
The paper describes experimental investigations of thermal and physical characteristics pertaining to material specimens which has been used for manufacturing the proposed heating device for heat supply system of a field medical hospital. The type of the given material has been determined that is  polyvinyl chloride.A warm-up period required for the heating device and estimation of time required for installation of a heating system for successful operation of the field hospital have been determined and executed in the paper.